Analysis on bacterial community structure of new and old fermented pit mud of Shedian Liquor. Issue 1 (31st December 2022) - Liu, Yanbo; Xu, Mingyue; Zhao, Zhijun; Wu, Junyi; Wang, Xian; Sun, Xiyu; Han, Suna; Pan, Chunmei
Abstract: The richness and diversity of bacterial community in the fermented pit mud from the new and old distilleries of Shedian Liquor were analysed via the Illumina Miseq PE300 high-throughput sequencing technology, so as to further understand the differences of bacterial community structure in fermented pit muds with different pit ages. The results show that the bacterial community is mainly distributed into five dominant phyla (> 1.0%): Firmicutes, Synergistes, Bacteroidetes, Proteobacteria and Verrucomicrobia . There are 13 dominant genera (> 1.0%), of which Lactobacillus is dominant in both samples with a higher content in the new pit (61.12%) and lower in the old pit (1.15%). Caproiciproducens accounting for 43.53% and Syntrophomonas accounting for 6.20%, norank_f__Family_XIV (17.68%), Aminobacterium (17.68%), Sedimentibacter (1.89%), Caldicoprobacter (1.52%) and Sporanaerobacter (1.29%) are the dominant bacteria in the old pit mud. Bacillus accounting for 6.02%, Bacteroides (6.27%), Akkermansia (1.51%), Hydrogenispora (2.15%) and norank_f__Bacteroidales_S24-7_group (1.15%) are the dominant bacteria in the new pit mud. The results showed that there is a great difference in the bacterial community structure of in the new and old pit mud. In addition, compared with the bacterial community composition in the pit mud of Luzhou flavour Baijiu in Sichuan, it was found that the microorganisms that formed caproic acid and butyric acid were different.